Differential Efficacy of B-Ultrasound Combined with Molybdenum Target Detection Mode for Breast Cancer Staging and Correlation of Blood Flow Parameters with IGF-1 and IGF-2 Expression Level and Prognosis. (24th June 2022) - He, Huiliao; Zhang, Guifan; Zhou, Haixian; Lin, Chunyang; Xu, Qun; Liu, Ruixing; Yu, Beibei; Zhou, Xiuping; Wang, Zhejin; Xu, Zhihua; Lin, Lejing
Abstract : The study investigates the diagnostic efficacy of ultrasound combined with the molybdenum target mode in breast cancer staging and the relationship between blood flow parameters and the expression of insulin-like growth factor 1 (IGF-1) and factor 2 (IGF-2) and prognosis. A total of 96 patients admitted to hospital from January 2020 to January 2021 are included in the breast cancer group, and 58 patients admitted to our hospital during the same period are included in the control group, who are diagnosed with benign breast lesions. All patients receive clinicopathological diagnosis, ultrasound detection, and X-ray molybdenum detection. Ultrasound detection, molybdenum target detection, ultrasound combined with the molybdenum target detection mode, and clinicopathological diagnosis results are compared. B-ultrasound combined with the molybdenum target detection mode has high efficiency in diagnosing breast cancer and differentiating pathological stages. Besides, blood flow parameters of patients are closely related to IGF-1 and IGF-2, and IGF-1 and IGF-2 expressions are closely related to the prognosis of patients. Subsequent diagnosis of the disease degree of breast cancer patients can be carried out by ultrasound combined with the molybdenum target detection mode. In addition, the expression of IGF-1 and IGF-2 in patients can be monitored to improve the clinical diagnosis and treatment plan to improve the prognosis of patients, which has a high clinical application value and is worth promoting.